2020
DOI: 10.1021/acsami.0c16855
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Monitoring of Small Strain for Timbre Recognition via Ductile Fragmentation of Functionalized Graphene Multilayers

Abstract: Sensitivity and linearity are two key parameters of flexible strain sensors. Although the introduction of microstructures (e.g., channel crack inspired by the geometry of the spider's slit organ) can effectively improve the sensitivity, the sudden breakage of the conductive path in turn leads to poor linearity. In practical applications, in order to achieve precise detection of subtle strains, high sensitivity and high linearity are required simultaneously. Here, we report a strain sensor design strategy based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
(69 reference statements)
0
16
0
Order By: Relevance
“…The first factor is the connectivity variation in SCNTNs, which is often considered as a main reason for resistance change in many piezoresistive sensors. [ 21,51,52 ] However, the case was different in this work. It was found that the topology of an SCNTN retained nearly unchanged when the gas velocity was in its detection range, and thus no resistance change should be generated if they were caused by the connectivity changes.…”
Section: Resultsmentioning
confidence: 78%
“…The first factor is the connectivity variation in SCNTNs, which is often considered as a main reason for resistance change in many piezoresistive sensors. [ 21,51,52 ] However, the case was different in this work. It was found that the topology of an SCNTN retained nearly unchanged when the gas velocity was in its detection range, and thus no resistance change should be generated if they were caused by the connectivity changes.…”
Section: Resultsmentioning
confidence: 78%
“…Currently, with the rapid development of soft electronic technologies, the application of flexible strain sensors tends to be increasingly extensive, including electronic skins, human-computer interactions, physiological parameter monitoring, , soft robots, , and other high-tech fields . To fabricate these sensors, various transduction mechanisms, such as piezoresistive, capacitive, piezoelectric, triboelectric, liquid metal, etc., have been adopted. On the basis of the above mechanisms, two main types of sensors have been widely developed: particular structural types and functional material types. The former type includes serpentine, wrinkle, pillar, crack, and interlock, offering advantages such as high sensitivity, low hysteresis, and fast response.…”
Section: Introductionmentioning
confidence: 99%
“…, ε : 0–5%, GF < 100), which cannot meet the requirements of dynamic strain sensing yet. As for the existing strain sensors that have favorable dynamic sensing ability, they generally possess a limited stretchability ( ε < 2%) 2,3,38,39,47 and a relatively narrow frequency detection range (<1000 Hz), 3,38,39,69 which can't be applied in scenarios such as concerning ultrahigh frequency as well as small/large strains simultaneously involved.…”
Section: Resultsmentioning
confidence: 99%
“…21,33,35 However, microcracking-based strain sensors generally have low stretchability due to the intrinsic lack of flexibility in the strain-sensing layer. 2,3,19,30,32,38,47 On the other hand, several strategies have been developed to improve the stretchability of strain sensors, e.g. , introduction of one-dimensional (1D) or two-dimensional (2D) conductive nanomaterials into the strain-sensing layer and/or design of stretchable surface structures ( e.g.…”
Section: Introductionmentioning
confidence: 99%